Uji Penetrasi Spesimen Pada Sungkup Helm Berbahan Biokomposit Sebagai Bahan Alternatif Pengganti Helm - Boy Rollastin (Politeknik Manufaktur Negeri Bangka Belitung, 2018)
The correct function of helmets is to protect motorcycle riders from head injuries during accident and head collision. Most of helmets existing in markets are produced by helmet factories. The price of used materials is quite high because those materials are still imported from overseas. It causes the increasing of helmet production cost and the helmet prices in the market become quite expensive. This research aims to find how a biocomposite material (85 % PP, 10 % husk of rice and 5 % MAPP) can be used as an alternative replacement material for helmet lid preparation on the condition of passing the SNI standar test, namely the penetration test. The testing process is carried out by using the test tools referring to SNI 181-2007. The results of penetration test with thickness of 4 mm showed that the speciment can not be penetrated by indenter in accordance with the requirements of SNI 1811-2007. So that the testing can be used as a reference for alternative materials to make a standard helmet lid.